Evaluasi Kinerja Parkir pada Kawasan Wisata Air Terjun Batu Mahasur, Kabupaten Gunung Mas, Kalimantan Tengah - Averro G. L. Rutih, Franzois; Parasian Silitonga, Sutan; Murniati, Murniati (MAN 4 Kota Pekanbaru, 2026)
The Batu Mahasur Waterfall tourist area is a strategic tourism asset of Gunung Mas Regency that experiences increasing visitor numbers, particularly during peak periods, which may affect parking performance and vehicle circulation. This study aims to evaluate the parking performance of the Batu Mahasur Waterfall tourist area by analyzing key parking characteristics, including parking volume, accumulation, turnover, occupancy rate, and parking index. The study employed primary data obtained from field parking surveys and secondary data in the form of site layout plans. The results indicate that the existing parking facilities are generally sufficient to accommodate current visitor demand, as no critical parking saturation was identified. However, several improvements are still required to enhance parking efficiency and service quality, particularly through optimization of parking layout and management strategies to support sustainable tourism development.